Creep properties of biodegradable Zn-0.1Li alloy at human body temperature: implications for its durability as stents. Issue 9 (2nd September 2019) - Zhu, Suming; Wu, Chengcheng; Li, Guannan; Zheng, Yufeng; Nie, Jian-Feng
ABSTRACT: This is the first report on creep properties of biodegradable zinc alloys at human body temperature. The extruded Zn-0.1Li (wt.%) alloy exhibits appreciable creep deformation at 37°C under stresses ranging 80–230 MPa within 500 h. The creep deformation at low stresses (80–155 MPa, about 0.4–0.8 yield strength) is characterized by a stress exponent of about 4 and an activation energy close to that for self-diffusion of zinc, which are typical of dislocation creep. The implications of creep at human body temperature for durability of biodegradable zinc alloys as stents are discussed. GRAPHICAL ABSTRACT: IMPACT STATEMENT: This is the first report on creep properties of biodegradable zinc alloys at human body temperature. It is demonstrated that creep resistance is another crucial parameter in the design of biodegradable Zn alloys.